AB0463 Clinical Characteristics of Elderly Patients with Primary Sjögren's Syndrome. (15th July 2016) - Nakanishi, K.; Kinjo, M.
Abstract : Background: Sjögren's syndrome is a common autoimmune disorder with the majority of cases occurring in midlife. Although the clinical presentation of primary Sjögren's syndrome (pSS) is known to differ by age, clinical characteristics of elderly patients with pSS have not been well described. Objectives: To identify clinical characteristics of patients with pSS based on age group. Methods: We retrospectively identified all patients with biopsy-proven lymphocytic sialadenitis and/or positive anti-SSA/Ro antibody who were treated at a tertiary medical center in Japan between 2005 and 2015. Data were collected on their clinical and laboratory features. Definite pSS was defined by the fulfilled American-European Consensus (AEC) criteria for pSS and probable pSS was determined by any 3 of the 6 AEC criteria without other collagen diseases. Clinical and laboratory characteristics of patients aged 60 years or older were compared with those of their younger counterparts. Results: We identified 402 Japanese patients with biopsy-proven lymphocytic sialadenitis and/or positive anti-SSA/Ro antibody. 147 (37%) had pSS, 36 (9%) were undifferentiated, and 219 (54%) had at least one or more antinuclear antibody-associated collagen diseases. The median age of the pSS patients was 52 years (range 17–89); 41% (60 patients) were aged 60 years or older, and 91% were female (Table ). Compared to the younger age group, the older patients were more likely to have dry mouth, primary biliary cirrhosis, lymphoma and thrombocytopenia. The younger patients had a greater likelihood of arthritis and a photosensitive rash (p<0.05). Conclusions: Clinical characteristics of pSS may differ between younger and elderly patients. In elderly patients with pSS, careful evaluation for coexisting primary biliary cirrhosis or lymphoma is recommended. References: Chudwin DS, Daniels TE, Wara DW, et al: Spectrum of Sjögren's syndrome in children. J Pediatr 98:213, 1981. Vitali C, Bombardiere S, Jonsson R, et al: Classification criteria for Sjögren's syndrome: A revised version of the European criteria proposed by the American-European Consensus Group. Ann Rheum Dis 61:554, 2002. Acknowledgement: We thank Dr. Thomas Lynn Hurt and Kimitoshi Yamaguchi (database). Disclosure of Interest: None declared